Systematic Reviews and Meta-Analyses - ISICAM ISICAM; Mahdi BA; Purnamasari Y; Fajar JK; Raymond Pranata; Emir Yonas (The Indonesian Heart Association, 2018)
Systematic Reviews and Meta-Analyses; Abstracts of the 10th Indonesian Society of Interventional Cardiology Annual Meeting Jakarta, 23-25 November 2018